Urban-rural disparities in travel during the COVID-19 pandemic: The case study of Serbia - Zeljković, Marija (ERDKUNDE, 2022)
In the past two years, the spread of the COVID-19 has affected large parts of economic and social life globally, especially the tourism industry, due to the restrictions on mobility. The pandemic caused uneven regional consequences. In addition to the differences in the number of infected persons, the mortality rate, and the number of vaccinated between individual countries, disparities between rural and urban areas are particularly evident. Fundamental differences in transport infrastructure and mobility behavior between urban and rural populations suggest differences in risk perception and future travel behavior. However, urban-rural disparities in travel behavior during the COVID-19 pandemic have hardly been explored so far, and this study aims to help fill this gap. The aim of this paper is to investigate the changes and differences in travel risk perceptions and travel behavior of urban and rural residents under the influence of the pandemic. Analyses were conducted based on an online survey data collection in June 2021 among 399 urban and 260 rural residents of Serbia. The results showed differences in travel intentions, travel frequency, and destination choice between urban and rural residents, as well as a preference for domestic tourism and short-haul travel. This study can serve as a guideline for future research on the urban-rural dichotomy regarding travel during the COVID-19 pandemic and as a reference point for comparative studies on urban-rural differences and tourism in different countries and geographical regions.